AD, Volume 8, n° 4, 1983 - Full Issue (Africa Development, 1983)
CONTENTS «South-South Cooperation, the Lagos Plan of Action and Africa's Independence» A. BENACHENHOU ......................... 5 «Le Plan d'Action de Lagos et la Banque Mondiale - Etude Comparative des deux points de vue sur l'Alimentation et l'Agriculture en Afrique» T. MKANDAWIRE ......................... 20 «Distribution and Labor Market Segmentation under Capitalism Guy C.Z. MHONE ............................... 35 «Employment and Income Generation in the Petty Commodity Sector of the Urban Economy: the Case of the Central Region of Ghana» P.W.K. YANKSON ..................... 75 «Towards Renegotiating the Lome Regime: Some (Non-Policy) Options Considered» Nantang JUA ....................... 97 BOOK REVIEWS World Economic Outlook 1983 - A Survey by the Staff of the I.M.F. Occasional Paper No. 21; IMF, Washington D.C., 1983 — 242pp. S8 Dr. Mbui WAGACHA .......................... 123 FOCUS ON RESEA PLEINS FEUX SUR LES INSTITUTS DE RECHERCHE ET DE FORMATION Centre National de Coordination et de Planification de la Recherche Scientifique et Technique ..................127 BOOKS RECEIVED ......................... 130